"تصميم و تنفيذ نظام قياس درجة الحموضة لمختلف المحاليل الكيميائية" - خولة, بصغير; وريدة, عدانة; قطر الندى, بوزنادة (University of El-Oued, 2020)
"The study presented in this thesis aims to design and implement a pH measurement system for various chemical solutions, where the theoretical aspects related to pH were discussed and explained and its various sensors were presented, as well as their features and characteristics. First, the design process and simulation of the proposed system using a program Proteus and a software code to manage the various units used, then it was implemented secondly in reality using the Arduino board and the pH sensor known as E-201PH and the inclusion of the feature of measuring temperature and humidity using the DHT11 sensor and the date and time using the DS1307 RTC circuit and then calibrating the system using buffer solutions, The results obtained through simulation and implementation showed their conformity with each other and acceptable measurement accuracy was obtained. They discussed how to improve accuracy and include additional features to develop its use in the process of tracking the pH of chemical reactions." "تهدف الدراسة المقدمة في هذه المذكرة إلى تصميم وتنفيذ نظام قياس ال pH لمختلف المحاليل الكيميائية ، حيث تمت مناقشة و شرح الجوانب النظرية المتعلقة بدرجة الحموضة و عرض مختلف الحساسات الخاصة به و كذا مميزاتها و خصائصها ، قد تمت أولا عملية التصميم و محاكاة النظام المقترح بإستخدام برنامج Proteus و کود برمجي لإدارة مختلف الوحدات المستعملة ، ثم تم تنفيذه ثانيا في الواقع بإستخدام لوحة Arduino و حساس pH المعروف ب E - 201PH و إدراج ميزة قياس درجة الحرارة والرطوبة بإستخدام الحساس DHT11 والتاريخ والوقت بإستخدام الدارة DS1307 RTC ثم معايرة النظام بإستخدام محاليل منظمة ، قد أظهرت النتائج المتحصل عليها من خلال عملية المحاكاة و التنفيذ تطابقها مع بعضها كما تم الحصول على دقة قياس مقبولة . تمت مناقشة كيفية تحسين الدقة و إمكانية إدراج ميزات إضافية لتطوير إستعماله في عملية تتبع درجة حموضة التفاعلات الكيميائية "
Génie chimiqueمذكرة ماستر تخصص
Keywords: درجة الحموضة ، أردوينو، بروتس ، محاليل منظمة ، نظام القياس .; pH , Arduino , Proteus, buffer solutions , measurement system ,.